1984
DOI: 10.1016/0014-5793(84)80884-4
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin binding to human spectrin

Abstract: Calmodulin is shown to interact with human spectrin dimer. The binding was highly calcium-dependent and observed in two different kinds of experiments. Firstly, affinity chromatography of calmodulin on a Sepharose 4B column with immobilized spectrin, and secondly, partition in aqueous two-phase polymer systems. In the column experiments stoichiometric amounts of calmodulin were retained on the spectrin-Sepharose column when micromolar concentrations of calcium were present. The calmodulin bound could be eluted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…To assess whether calmodulin interferes with the binding of filamentous actin to spectrin, we did direct binding studies using the aqueous two-phase partition technique (Backman, 1985). This technique has proven to be well-suited for studying weak interactions, and we have previously used it to characterize the relatively weak association between calmodulin and spectrin (Berglund et al, 1984(Berglund et al, , 1986. It is clearly seen in Figure 5 that increasing amounts of filamentous actin reduced the fraction of calmodulin bound to spectrin; at 10 µ actin in the lower phase, 60-70% of bound calmodulin was released.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess whether calmodulin interferes with the binding of filamentous actin to spectrin, we did direct binding studies using the aqueous two-phase partition technique (Backman, 1985). This technique has proven to be well-suited for studying weak interactions, and we have previously used it to characterize the relatively weak association between calmodulin and spectrin (Berglund et al, 1984(Berglund et al, , 1986. It is clearly seen in Figure 5 that increasing amounts of filamentous actin reduced the fraction of calmodulin bound to spectrin; at 10 µ actin in the lower phase, 60-70% of bound calmodulin was released.…”
Section: Resultsmentioning
confidence: 99%
“…Calmodulin, which is known to bind to erythrocyte spectrin (Berglund et al, 1984(Berglund et al, , 1986Husain et al, 1984) and to other spectrins (Glenney et al, 1982), inhibits the fragmenting activity of spectrin on actin. The inhibition is calcium dependent since no reduction of fragmentation was observed when calcium was replaced by magnesium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although interaction between CaM and spectrin is weak, with the reported Kd ranging from 2-22 ,uM (22,23,25), FIGURE 5 Effect of CON-A on MAL-6-labeled CaM in solution and bound to ghosts. Tau is the apparent rotational correlation time.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the viscosity decreased with further increases in Ca2" concentration. A possible role for CaM in regulating skeletal protein interactions was also suggested by studies that showed that this protein can bind to the erythrocyte membrane (13,14) as well as to various skeletal proteins (spectrin monomer [5,15,16], af3 spectrin dimer [14,17], and protein 4.1 [18]). Gardner and Bennett (19) The property of membrane deformability that determines the extent of membrane deformation that can be induced by a defined level of applied force was also measured by the ektacytometer.…”
Section: Introductionmentioning
confidence: 99%